Feasibility Study Hakmaz Taba Syariah Hotel Cooperate with PT Grahawita Santika - Maruszama, Mahfidarwan Akbar; Darmansyah, Asep (Journal of Business and Management, 2016)
Abstract.Hakmaz Taba Syariah Hotel is one of the hotels in Lubuklinggau who participate actively welcome the tourists who come to Lubuklinggau.Hakmaz Taba Syariah Hotel located at Jl. Yos Sudarso No 28 Lubuklinggau, South Sumatera, Indonesia. The hotel established since 1997. Hakmaz Taba Syariah Hotel is a hotel with the nuances of Islamic, elegant minimalist decor blends with local culture. The hotel has 48 rooms with facilities such as restaurant, cafe, swimming pool, children play ground, outdoor garden party, ballroom, ATM Center, and meeting room. There are a couple of things and the perceived problems that need to be repaired. Some of the problems being experienced are owner does not have experience in the hospitality sector, cause the hotel is not well controlled, the financial statements hotel is not recorded properly while already using the system / software, the marketing activity is not running, and the human resources are difficult to find in South Sumatra.Lubuklinggau have an interesting developments, competitors can lead to decreased number of occupancy of Hakmaz Taba Syariah Hotel. Because of it, the owners had approached and meetings with some of the operators of the hotel management, which are Starwoods Hotels, Swiss-Belhotel, Accor, Tauzia, Santika, and Dafam. The results of the meeting with the hotel management operator and conclusions given by the hotel owners indicate a match with PT Grahawita Santika (GWS). All problem identification in this paper will be solved using economical feasibility study.A business feasibility study can be defined as a controlled process for identifying problems and opportunities, determining objectives, describing situations, defining successful outcomes, and assesing the range of costs and benefits associated with several alternatives for solving a problem. This study is used to support the decision-making process based on a cost benefit analysis of the actual business or project viability.It should help the company to find out does this invesment is the correct decision to do. The author will take the approach of the financial feasibility of using several methods such as NPV and IRR calculation, assisted by a brief explanation of market feasibility and legal feasibility The theoritical framework of this final assignment is based on various source which are text books, internet data and secondary data that collected from the company. Those source are used to find some supportive theories, information, and data to accomplish this final project.Formula that could be supportive for this final project are Net Present Value (NPV), Internal Rate of Return (IRR), Weighted Average Cost of Capital (WACC), and other formulas that related to financial feasibility.After analyzing the initial investment, income statement, statement of cash flow of the project, Author finally meet the conclusion that the project is not feasible to do. The project stated not feasible because the Net Present Value of the project is negative, Payback Period occur in the 9th year, and the Internal Rate of Return are lower than the discount rate which is Weighted Average Cost of Capital. If the owners still have the desire to run the project, there are some things that need to be calculated.Keywords : Financial, Hotel, Investment, Tourism, Lubuklinggau, Indonesia, Feasibility